Cryptosporidiosis In Man And Animals In Al-Tameem Province/ Iraq. - Kadir, Mohammed Abdul-Aziz (The Iraqi Journal of Veterinary Medicine, 2004)
This study was conducted on 790 stool samples from infants and young children up to ten years of age, suffering from acute diarrhea who attended Kirkuk Pediatric Hospital, from the beginning of August 1999 of July 2000. The animal study was carried on 160 lambs, 130 calves and 110 kids suffering from diarrhea in private veterinary clinics in Al-Tameem province. The rate of acute cryptosporidiosis was (10%). There was no significant difference between the two sexes . It was higher in winter and spring than summer and autumn months . The infection rate was higher among children in contact with poultry than those in contact with cattle and sheep and was lowest among those not in contacts with animals. The distribution of cryptosporidiosis among domestic animals was as follows: in lambs, calves and kids the infection rates were 20%, 19.2% and 23.6% respectively.